1993
DOI: 10.1002/j.1460-2075.1993.tb05948.x
|View full text |Cite
|
Sign up to set email alerts
|

Kettin, a large modular protein in the Z-disc of insect muscles.

Abstract: Z‐discs of insect flight muscle contain a large protein of 500–700 kDa. Monoclonal antibodies label an epitope in the molecule at the Z‐disc in Drosophila and Lethocerus (waterbug). A partial cDNA of 1.6 kb from the Drosophila gene has been cloned and sequenced. The corresponding amino acid sequence has a modular structure composed of four conserved repeats of 95 amino acids homologous to immunoglobulin C2 domains (called class II domains in muscle proteins), separated by less conserved linker sequences of 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 46 publications
3
104
0
Order By: Relevance
“…Localization of Ce-kettin on the thin filaments was proximal to the dense bodies and was similar to that of kettins from insects (Lakey et al, 1990(Lakey et al, , 1993van Straaten et al, 1999) and crayfish (Maki et al, 1995;Fukuzawa et al, 2001), which are localized to the side of the Z-discs. In addition, the N terminus of insect kettin is located within the Z-discs (van Straaten et al, 1999).…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Localization of Ce-kettin on the thin filaments was proximal to the dense bodies and was similar to that of kettins from insects (Lakey et al, 1990(Lakey et al, , 1993van Straaten et al, 1999) and crayfish (Maki et al, 1995;Fukuzawa et al, 2001), which are localized to the side of the Z-discs. In addition, the N terminus of insect kettin is located within the Z-discs (van Straaten et al, 1999).…”
Section: Discussionsupporting
confidence: 55%
“…Previously, the full-length kettin has been demonstrated to bind to actin filaments with high affinity (Maki et al, 1995;van Straaten et al, 1999), and the stoichiometry has suggested that one Ig-repeat may bind one actin monomer in the filament (van Straaten et al, 1999). This was also supported by the report that a single Ig-repeat of kettin is capable of binding to actin filaments (Lakey et al, 1993). However, our results show that the four C-terminal Ig-repeats (KETN-CT1) bind to actin at lower stoichiometry than one repeat per one actin monomer, and, interestingly, that the adjacent non-Ig region augments both affinity and stoichiometry for binding to actin.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations